Cryo‐EM structure of native human uromodulin, a zona pellucida module polymer. (16th November 2020) - Stsiapanava, Alena; Xu, Chenrui; Brunati, Martina; Zamora‐Caballero, Sara; Schaeffer, Céline; Bokhove, Marcel; Han, Ling; Hebert, Hans; Carroni, Marta; Yasumasu, Shigeki; Rampoldi, Luca; Wu, Bin; et al.
Abstract: Assembly of extracellular filaments and matrices mediating fundamental biological processes such as morphogenesis, hearing, fertilization, and antibacterial defense is driven by a ubiquitous polymerization module known as zona pellucida (ZP) "domain". Despite the conservation of this element from hydra to humans, no detailed information is available on the filamentous conformation of any ZP module protein. Here, we report a cryo‐electron microscopy study of uromodulin (UMOD)/Tamm–Horsfall protein, the most abundant protein in human urine and an archetypal ZP module‐containing molecule, in its mature homopolymeric state. UMOD forms a one‐start helix with an unprecedented 180‐degree twist between subunits enfolded by interdomain linkers that have completely reorganized as a result of propeptide dissociation. Lateral interaction between filaments in the urine generates sheets exposing a checkerboard of binding sites to capture uropathogenic bacteria, and UMOD‐based models of heteromeric vertebrate egg coat filaments identify a common sperm‐binding region at the interface between subunits. SYNOPSIS: Urinary glycoprotein uromodulin (UMOD) forms filaments via its C‐terminal zona pellucida (ZP) module, a conserved building block of many polymeric extracellular proteins. Cryo‐EM of native human UMOD filaments and structurally‐related vertebrate egg coat material sheds light on the atomic architecture of ZP module polymers and how it may contribute to their many biological functions. Comparison of the filament structure with that of the UMOD precursor explains how propeptide dissociation starts polymerization by triggering intermolecular interaction between ZP modules. The linker between the ZP‐N and ZP‐C moieties of the ZP module undergoes a dramatic conformational change during polymerization. In the filament, each UMOD subunit embraces the ZP‐C and ZP‐N domains of the neighboring molecules, giving rise to a highly stable helix made up of interlocked subunits with a twist angle of 180 degrees. UMOD filaments can assemble into a multivalent molecular "Velcro" that facilitates the capture of uropathogenic bacteria by the N‐terminal region of the protein. By adopting an architecture similar to the UMOD homopolymer, heteromeric egg coat filaments present sperm‐binding regions at the interface between subunits. Abstract : Insights into the architecture of uromodulin filaments involved in the capture of uropathogenic bacteria, and structurally‐related vertebrate egg coat material, suggest how a widespread extracellular polymerization module can support multiple functions.